2016
DOI: 10.1002/em.22017
|View full text |Cite
|
Sign up to set email alerts
|

No cytotoxicity or genotoxicity of graphene and graphene oxide in murine lung epithelial FE1 cells in vitro

Abstract: Graphene and graphene oxide receive much attention these years, because they add attractive properties to a wide range of applications and products. Several studies have shown toxicological effects of other carbon‐based nanomaterials such as carbon black nanoparticles and carbon nanotubes in vitro and in vivo. Here, we report in‐depth physicochemical characterization of three commercial graphene materials, one graphene oxide (GO) and two reduced graphene oxides (rGO) and assess cytotoxicity and genotoxicity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 48 publications
5
65
1
2
Order By: Relevance
“…Lateral size, specific surface area, C/O and C/H ratios were determined using transmission electron microscopy (TEM), Brunauer–Emmet–Teller (BET) and combustion elemental analysis, respectively. a Adapted from Bengtson et al [26]. …”
Section: Resultsmentioning
confidence: 99%
“…Lateral size, specific surface area, C/O and C/H ratios were determined using transmission electron microscopy (TEM), Brunauer–Emmet–Teller (BET) and combustion elemental analysis, respectively. a Adapted from Bengtson et al [26]. …”
Section: Resultsmentioning
confidence: 99%
“…15,16 The safety and biocompatibility of GO has been a subject of intense research in the scientific community. The reports have been controversial, some reported that GO is nontoxic, even in a high dose of 200 µg/mL after 24 hours of exposure to cells lines, 17,18 while others reported that GO interacted with DNA and induced mutagenesis in the MDA-MB-231 human breast cancer cells. 19 In fact, GO, even at the low dose of 10 µg/mL, altered gene expression patterns and caused cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was observed that the cells exposed to graphene materials for 24 h did not affect cytotoxicity in terms of cell viability and cell proliferation. In addition, no genotoxicity was observed by Comet assay analysis in cells exposed to graphene for 3 and 24 h [38].…”
Section: In Vitro Studies On Healthy Primary Cells or Cell Linesmentioning
confidence: 90%
“…In vitro genotoxicity studies involving healthy primary cells or cell lines. Comet assay, qRT-PCR, DNA methylation assay [35] GQDs (lateral size of 40 nm, thickness of 2 nm) NIH-3T3 3 and 24 h 5, 50 μg ml −1 IF for XRCC4 and OGG1 expression, flurimetric DCFH-DA assay [36] GO-S (100 nm), GO-L (10 μm) BEAS-2B 0-12 h 12.5, 25, 50 μg ml −1 Alkaline Comet assay [37] LA-PEG-GO (100-200 nm), PEG-GO (50-150 nm) and PEI-GO (200-500 nm) HLF 2, 4, 12, 24 h 1, 10, 50, 100 μg ml −1Comet assay, SOD measurement, flurimetric DCFHmg ml −1 Flurimetric DCFH-DA, Comet assay[38] …”
mentioning
confidence: 99%